Pengaruh Profitabilitas, Solvabilitas, Opini Audit Dan Ukuran Kantor Akuntan Publik Terhadap Audit Delay Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022 - Nafa Dwi Ananda; Tasya Tasya; Santi Laura Ursula Sinaga; Arie Pratania Putri; Alisastra Dason Silalahi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study/research is to distinguish how profitability, solvency, audit opinion, and public accounting firm size are symptomatic/affected by audit delay in pharmaceutical sub-sector organizations listed on the Indonesia Stock Exchange in 2019-2022. This deep dive into research includes quantitative techniques using purposive testing to address specific examples. The exploratory test included 36 perceptions of pharmaceutical sub-sector organizations listed on the Indonesia Stock Exchange. In this research, E-views model/type 12 programming was used. In the research examination conducted, it is seen that individually/partially, profitability has a relevant impact on audit delay. However, the solvency factor, audit opinion and the size of the public accounting firm individually/partially, profitability has no impact on audit delay factors. Other research in groups / simultaneously, profitability, solvency, audit opinion, and the size of the public accounting firm have a relevant impact on audit delay factors. Keywords: Profitability, Solvency, Audit Opinion, Public Accounting Firm Size, Audit Delay